Advanced characterization method of Nylon 12 materials for application in laser sinter processing - Rüsenberg, Stefan; Schmid, Hans-Joachim (International Conference of the Polymer-Processing-Society (PPS))
Laser Sintering is a powder based additive manufacturing technology. The amount of used powder, which is not sintered, can be refreshed and used for further building jobs. Due to cost reduction, better mechanical properties and a simpler processing it is reasonable to combine virgin and used powder for part manufacturing. During the building time the powder is thermally loaded and its structure is changed. State of the art in laser sintering is a defined powder ratio. Since the powder ageing depends on the individual history of sintering, this procedure cannot ensure a defined powder quality. However, for a serial production it is necessary to characterize the raw material, as well as all other steps along the process chain, in order to ensure a high reproducibility and reliability. Rheological, physical and particle properties are considered to correlate powder and chosen material properties. Different powder qualities adjusted by the Melt Volume Rate (MVR) are tested using promising rheological properties like viscosity or molecular weight. Investigations about powder bed density, bulk properties as well as thermal characterization complement the experimental setup. These parameters are correlated with mechanical, electrical, thermal and physical material properties of laser sintered parts. The most important influencing factors along the process chain are kept constant. At the end a procedure is shown to obtain a defined powder quality. This procedure will be transferred to other materials and will be tested using other laser sintering machines of the same type as well as other types.